Migration, Covid, Remittances and Economic Growth in the Baltic States: a Regional Perspective - Přívarová, Magdaléna, 1955-
Vplyv remitencií na hospodársky rast. Emigrácia a remitencie v Pobaltí. Geografia remitencií v Pobaltí.